THE UTILIZATION OF COMPLEX PROPORTIONAL ASSESSMENT (COPRAS) IN DETERMINING THE SELECTION OF THE BEST SPEAKER - Muhammad Rafli Nur Alam; Richki Hardi; Sumardi Sumardi (Multica Science and Technology, 2022)
Decision-making in choosing the appropriate sound system involves numerous considerations to achieve acceptable outcomes or quality. There are many critical factors influencing the selection of speaker models, such as the required program features, brand, design, power, and price. In this study, we introduce the Complex Proportional Assessment (COPRAS) method as a solution for making effective and high-quality decisions when selecting the best alternatives based on predefined criteria. The COPRAS method is employed to analyze various different alternatives and estimate their utility values. The case study presented in this research involves identifying the best alternatives according to the criteria within the context of sound systems. The COPRAS method aids in evaluating alternatives by taking into account the relative weights of each relevant attribute. Consequently, the use of the COPRAS method in selecting the best sound system has proven to be effective and beneficial. This method assists in addressing complexity, enhancing objectivity, and yielding more informative and accurate decisions.